Vibrotactile Data Physicalization: Exploratory Insights for Haptization of Low-resolution Images - Bastidas Cuya, Franklin Giovani; Martins Guarese, Renan L.; Johansson, Carlos Guilherme; Giambastiani, Mariane; Iquiapaza, Yhonatan; de Jesus Oliveira, Victor Adriel; Nedel, Luciana; Maciel, Anderson (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2021)
We present a visuo-haptic interaction approach that augments the visual experience of graphic data visualization with meaningful vibrotactile information. The user of our interface explores charts and graphs on a conventional video monitor or other displays, e.g. projection, or printed paper. When a user touches the data visualization, an array of vibrotactile actuators placed at the joints on the back of their hand modulates frequency and amplitude to build signals that convey information, in a process of dynamic physicalization. We investigated the haptic perception of the method based on the change in the intensity of the simultaneous vibration and the distance between two variables being analyzed. For this, we assess a prototype of our interface in a user study (N=25) to understand how the stimulus is perceived and understood. Results show that different vibration intensities are recognized regardless of the spatial distance between them. The statistically significant difference in precision and response time between two values being haptically displayed shows it is possible to discriminate pieces of data with a faster response time as the percentage difference in intensity between them increases. Additionally, a heat map of the user interaction with the data represented by a square area shows that the user seeks to feel a single rendered data value on all actuators in the hand at once, rather than having two values rendered simultaneously on different fingers of the same hand.